Application of the scrum framework in non-software project management - Nikoghosyan, Marianna (My University, 2011)
Scrum is an agile project management approach that has been widely practiced in the software development projects. It has proven to increase quality, productivity, customer satisfaction, transparency and team morale among other benefits from its implementation. The concept of scrum is based on the concepts of incremental innovation strategies, lean manufacturing, kaizen, iterative development and so on and is usually contrasted with the linear development models such as the waterfall method in the software industry. The traditional approaches to project management such as the waterfall method imply intensive upfront planning and approval of the entire project. These sort of approaches work well in the well-defined stable environments where all the specifications of the project are known in the beginning. However, in the uncertain environments when a project requires continuous development and incorporation of new requirements, they do not tend to work well. The scrum framework was inspiraed by Nonaka’s article about new product developement and was later adopted by software development practitioners. This research explores conditions for and benefits of the application of scrum framework beyond software development projects. There are currently a few case studies on the scrum implementation in non-software projects, but there is a noticeable trend of it in the scrum practitioners’ community. The research is based on the real-life context multiple case study analysis of three different non-software projects. The results of the research showed that in order to succeed within scrum projects need to satisfy certain conditions – necessary and sufficient. Among them the key factors are uncertainty of the project environment, not well defined outcomes, commitment of the scrum teams and management support. The top advantages of scrum implementation identified in the present research include improved transparency, accountability, team morale, communications, cooperation and collaboration. Further researches are advised to be carried out in order to validate these findings on a larger sample and to focus on more specific areas of scrum project management implementation.